Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I'm trying to prove that

$|\cot (x+iy)|^2=\frac{\cos^2x+\sinh^2y}{\sin^2x+\sinh^2y}$

for $x+iy \in \mathbb{C} \setminus \pi\mathbb{Z}$.

I've tried to use the identities $\cos(iy)=\cosh y$ and $\sin(iy)=i\sinh y$, but I obtain

$|\cot (x+iy)|^2=\frac{\cos^2(x) \cosh^2 y+\sin^2(x) \sinh^2y}{\sin^2(x)\cosh^2 y+\cos^2(x)\sinh^2y}$

What did I miss?

share|improve this question

1 Answer 1

You have missed nothing except simplification

Using $\cos^2x+\sin^2x=\cosh^2y-\sinh^2y=1$, eliminate $\cosh y,\sin x$ from the numerator and $\cosh y,\cos x$ from the denominator.

$\cos^2x\cosh^2y+\sin^2x\sinh^2y=\cos^2x(1+\sinh^2y)+(1-\cos^2x)\sinh^2y=\cos^2x+\sinh^2y$

$\sin^2x\cosh^2y+\cos^2x\sinh^2y=\sin^2x(1+\sinh^2y)+(1-\sin^2x)\sinh^2y=\sin^2x+\sinh^2y$

Again, $\cos^2x+\sinh^2y=1-\sin^2x+\cosh^2y-1=\cosh^2y-\sin^2x$

and $\sin^2x+\sinh^2y=1-\cos^2x+\cosh^2y-1=\cosh^2y-\cos^2x$(this is another simplified form)

share|improve this answer
    
And $\cos^2(x)\cosh^2y+\sin^2(x)\sinh^2y=\cos^2x(1+\sinh^2y)+(1-\cos^2x)\sinh^2y$ thanks! –  Fuente Oct 24 '12 at 10:46
    
@Fuente, $\cosh^2y=1+\sinh^2y$, please find the updated answer. –  lab bhattacharjee Oct 24 '12 at 10:48
    
I know, it was a typo .) –  Fuente Oct 24 '12 at 10:50

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.